Anthocyanins from purple sweet potato alleviate doxorubicin‐induced cardiotoxicity in vitro and in vivo. Issue 9 (19th July 2021) - Tang, Sixue; Kan, Juan; Sun, Rui; Cai, Huahao; Hong, Jinhai; Jin, Changhai; Zong, Shuai
Abstract: In this study, anthocyanins were extracted and purified from purple sweet potato anthocyanins (PSPA) and the alleviative effect of PSPA on doxorubicin (DOX)‐induced cardiotoxicity was investigated. High Performance Liquid Chromatography‐Mass Spectrometry (HPLC‐MS) results showed that 10 kinds of substances were identified in PSPA and the PSPA was mainly composed of cyanidin (62.9%) and peonidin (21.46%). In in vitro experiments, PSPA reduced the excessive release of inflammatory factors (NO and TNF‐α) induced by DOX and decreased the secretion of trimethylamine oxide (TMAO), lactic dehydrogenase (LDH), and creatine kinase (CK) caused by myocardial injury. In in vivo experiments, PSPA inhibited the release of NO and MDA levels in heart tissue. Meanwhile, mice treated with PSPA decreased the levels of LDH, CK, TNF‐α, and TMAO in serum and heart tissue when compared with the DOX group. In addition, the histopathological results of the heart tissue also showed a protective effect of PSPA on the pathological changes in heart. These results provide a reference for the application of PSPA as a functional food to intervene in DOX‐induced cardiotoxicity. Practical applications: The effects of anthocyanins from purple sweet potato anthocyanins (PSPA) on doxorubicin (DOX)‐induced cardiotoxicity were investigated in vitro and in vivo. The results indicated that PSPA could significantly ameliorate DOX‐induced heart failure. The obtained results could provide the potential application of PSPA as an alternative therapy for cardiotoxicity caused by DOX in the functional food industry. Abstract : Anthocyanins from purple sweet potato anthocyanins (PSPA) were purified and identified by HPLC‐MS. The results showed that 10 kinds of substances were identified in PSPA and the PSPA was mainly composed of cyanidin (62.9%) and peonidin (21.46%). In vitro cell experiments showed that PSPA has a protective effect on cardiomyocyte damage induced by DOX. And the results of in vivo animal experiments showed that PSPA can alleviate the cardiotoxicity induced by DOX in mice. In addition, PSPA could significantly alleviate doxorubicin‐induced cardiotoxicity.